Pharmacist-led patient education on antiretroviral therapy: is it enough to improve adherence? - Squilanti, Ana Clara Fulanetti; De Oliveira, Fernanda Mariana; Mastroianni, Patricia Carvalho (Vitae, 2016)
Case presentation: A 58-year-old man with AIDS, under ART treatment for 12 years, presenting non-compliance due pharmacotherapy complexity and lack of knowledge regarding disease and treatment. A care plan including pharmaceutical and educational interventions was established during a 7-month follow up. The plan mainly contemplated individual educational interventions with a few adjustments in the pharmacotherapy. Improvement of adherence and increase in quality of life where achieved in the end of the interventions, but no clinical impact was observed. Conclusion: Although increase in self-care and compliance to ART were enhanced, less complex regimens decided in cooperation between pharmacists and physicians could achieve better outcomes and solve some adverse-effects.